2010
DOI: 10.1002/mnfr.200900583
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of antioxidant status following ingestion of green teas at different polyphenol concentrations and antioxidant capacity in human volunteers

Abstract: In a randomized cross-over study, 15 healthy volunteers consumed 500 mL of green tea (GTFT) with different solid contents (1.4, 1.6, 1.8 and 2.0 g/L) to induce a dose-response effect on plasma antioxidant capacity. Ingestion of GTFT 2.0 g/L significantly increased plasma reducing power (ferric reducing antioxidant power, FRAP) at 1 h (+2.9%; p<0.01), 2 h (+2.5%; p<0.05) and 4 h (+3.6%; p<0.01). GTFT 1.8 g/L showed statistical significance at 1 h (+4.3%; p<0.01) and 2 h (+4.4%; p<0.01), whereas GTFT 1.6 g/L was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Compared to tap water and alcohol-free white wine groups, ingestion of alcohol-free red wine caused significant increases in plasma TAC values and polyphenol concentrations 50 min after ingestion [116]. Similarly, a dose-dependent manner of the acute effects of green tea ingestion on plasma TAC was demonstrated in another randomized crossover study [119]. In these studies, the increase in plasma TAC was attributed to the polyphenols present in these foods and beverages.…”
Section: Antioxidant Intakes and Cvdmentioning
confidence: 99%
“…Compared to tap water and alcohol-free white wine groups, ingestion of alcohol-free red wine caused significant increases in plasma TAC values and polyphenol concentrations 50 min after ingestion [116]. Similarly, a dose-dependent manner of the acute effects of green tea ingestion on plasma TAC was demonstrated in another randomized crossover study [119]. In these studies, the increase in plasma TAC was attributed to the polyphenols present in these foods and beverages.…”
Section: Antioxidant Intakes and Cvdmentioning
confidence: 99%
“…It is important to mention that the solubility of CBZ is known to increase with an increase in pH, which might be a possible reason for enhanced bioavailability of CBZ when concomitantly administered with M [19,20]. Interestingly enough, the increased bioavailabilityrelated toxicity of CBZ was found to be absent with BT, which might have some relation to the in vivo antioxidant property of BT [21,22] while similar protection was found to be j o u r n a l o f f o o d a n d d r u g a n a l y s i s x x x ( 2 0 1 4 ) 1 e9 absent in M. Therefore, among the various combinations of beverages and CBZ used in this study, BT appears to be comparatively safe. Thus, from our observation, the presence of LJ or GFJ along with CBZ leads to increased bioavailability of CBZ.…”
Section: Parametermentioning
confidence: 93%
“…Pecorari et al [15] studied biomarkers of antioxidant status in 15 healthy volunteers after each volunteer consumed 500 mL of green tea with different solid counts (1.4, 1.6, 1.8, and 2.0 g/L). They observed that after consuming green tea with a solid count of 2.0 g/L, the total radical trapping antioxidant parameter of plasma was increased by 8.4% after 1 h of consumption of green tea; even after 4 h, the plasma antioxidant potential was still increased by 5.9% compared to the baseline.…”
Section: Tea or Coffee Consumption And The Antioxidant Capacity Of Bloodmentioning
confidence: 99%